Report on Recent Advances in Treatment Options through Vitamins (Bangladesh Journal of Medical Science, 2021)
Vitamins are the essential dietary components that are required in trace amounts by our body for the proper functioning of its biochemical processes and to prevent the deficiency diseases. The case of an infant having epileptic seizures at birth is discussed, which was found to be pyridoxine (vitamin B6) - dependent. It has been discovered through recent researches that vitamin K is involved in the immunology, atherosclerosis, inflammation and bone mineralization. Vitamin C is found to act as an anti-tumor agent when used intravenously in high doses. Recent researches have led us to understand that vitamins have a broader spectrum of functions than they are anticipated to have in our body and can be used to treat much more diseases when used alone, in combination or via different routes or in different concentrations or doses.Bangladesh Journal of Medical Science Vol.20(2) 2021 p.234-240